Membongkar Hadits Maudhu’ - Achmad Achmad (Jurnal Keislaman, 2020)
Abstract: The scholars' differed opinions about when the falsification of hadith began, people have falsified various hadiths with different motives and goals, especially for certain interests people can and dare to make false hadiths. Understanding the term hadith is a hadith that is based on the Messenger of Allāh Secara in a made-up and a lie, even though he did not say to do or set it. Using the hadith maudu is canceled, and it is forbidden to narrate it unless forced or work on the hadith to a scientific expert for examination. Based on existing historical data, the fabrication of hadith is not only done by Muslims but also carried out by non-Muslims with various motives and interests among other things. etcetera. Keywords: Hadith, Maudhu ’